7y+7=19y-3y+61

Since y is on the right side of the equation, switch the sides so it is on the left side of the equation.

19y-3y+61=7y+7

Subtract 3y from 19y.

16y+61=7y+7

Subtract 7y from both sides of the equation.

16y+61-7y=7

Subtract 7y from 16y.

9y+61=7

9y+61=7

Subtract 61 from both sides of the equation.

9y=7-61

Subtract 61 from 7.

9y=-54

9y=-54

Divide each term in 9y=-54 by 9.

9y9=-549

Cancel the common factor of 9.

Cancel the common factor.

9y9=-549

Divide y by 1.

y=-549

y=-549

Divide -54 by 9.

y=-6

y=-6

Solve for y 7y+7=19y-3y+61